HUBUNGAN PENGETAHUAN GIZI, AKTIVITAS FISIK DAN ASUPAN ZAT GIZI DENGAN STATUS GIZI PADA REMAJA DI SMK KECAMATAN GRESIK - Farradyna Dias Novianty; Desty Muzarofarus Sholikhah; Heri Purnama Pribadi (Ghidza Media Jurnal, 2021)
Background: Indonesia has three burdens of nutritional problems (triple burden), especially in adolescents, namely stunting, wasting and obesity as well as micronutrient deficiencies. East Java Province, the prevalence of obese adolescents aged 13-15 years is 13.3% and aged 16-18 years is 11.3%. Especially in Gresik Regency, the prevalence of thin adolescents aged 16-18 years is 9.41%, fat adolescents are 15.74% and obese adolescents are 7.47%. The problem of undernutrition and overnutrition, especially in adolescents can have a very bad impact on the sufferer. Objective: To analyze the level of nutritional knowledge, physical activity and nutrient intake with adolescents nutritional status of high school in Gresik District. Method: This research is a purposive sampling research with cluster sampling design. Respondents as many as 98. Data on respondent identity, knowledge of nutrition, physical activity and nutrient intake were taken through interviews with a questionnaire guide (Nutrition Knowledge, GPAQ and Recall). Antropometric data obtained through direct measurements. Statistical analysis was carried out bivariately with the Spearman Rank test ang multivariate with the Multiple Discriminant test. Result: The result of BMI/U are 73.5% good nutrition and 17.3% over nutrition. There is no relationship between nutritional knowledge and nutritional status (p value 0.323 > 0.05), there is no relationship between physical activity and nutritional status (p value 0.772 > 0.05), there is no relationship between nutrient intake and nutritional status (p value > 0.05). There is no relationship between knowledge of nutrition, physical activity, nutrient intake and nutritional status because the sig. value in the multiple discriminant test is > 0.05. Conclusions: There is no relationship between nutritional knowledge and nutritional status, there is no relationship between physical activity and nutritional status, there is no relationship between nutrient intake and nutritional status and there is no relationship between knowledge of nutrition, physical activity, nutrient intake and nutritional status.